MEN'S WAISTCOATS IN THE TRADITIONAL CLOTHING CULTURE OF ELAZIĞ - Kuru, Songül; Gür, Emel (Asos Eğitim Bilişim Danışmanlık San. Tic. Ltd. Şti., 2018)
The Anatolia is a region that has been home to many civilizations and therefore known as the cradle of civilizations. Distinctive cultural values of the Anatolia have been enriched thanks to its interaction with many cultures. In this regard, every region of the Anatolia has created its own cultural values. The Province of Elazığ has also developed a distinctive culture with its architecture, food culture, traditional handicrafts and clothes. Traditional clothes and clothing culture, which are material culture products, are still in use in some regions. Today's use of Elazığ traditional clothes varies in accordance with purpose. The elderly still wear şalvar baggy trousers , waistcoat the cepken and jacket. Men's clothing is a combination of şalvar-waistcoat-jacket and shirt. Descriptive method was used in the research made so as to analyze the use of men's waistcoats in the traditional clothing culture of Elazığ". Data had been acquired from Elazığ Ethnography Museum, the Family Union and Fırat University Folk Dances Association. Afterwards, data, i.e. waistcoats, were examined; waistcoats inventory was taken&studied; technical and model drawings were made&studied.

Onlarca medeniyete ev sahipliği yapmış olan Anadolu, medeniyetlerin beşiği olarak da adlandırılan bir coğrafyadır. Birçok kültürle etkileşim içinde olması kendine özgü kültür değerlerini zenginleştirmiştir. Bu bağlamda Anadolu'nun her yöresi, kendine özgü kültürel değerleri oluşturmuştur. Elazığ yöresi de; mimarisi, yemek kültürü, geleneksel el sanatları ve giyim kuşamıyla kendine özgü bir kültür geliştirmiştir. Maddi kültür ürünlerinden olan geleneksel giyinme ve giyim kültürü bazı yörelerimizde halen devam ettirilmektedir. Elazığ Geleneksel Elazığ erkek kıyafetlerinin günümüzdeki kullanımı, amaca göre değişiklik göstermekle birlikte, genellikle yaşlılar şalvar, cepken, yelek cepken ve ceketi halen kullanmaktadırlar. Erkeklerin kullandığı giysiler şalvar-yelek-ceket ve gömlek kombinin den oluşmaktadır. Elazığ yöresi geleneksel giyim kültüründe Erkek yeleklerinin incelenmesi amacı ile yapılan araştırmada betimsel yöntem kullanılmıştır. Veriler Elazığ Etnografya Müzesi, Aile Sandığı ve Fırat Üniversitesi Halk Oyunları Derneğinden elde edilmiş ve verileri oluşturan yelekler incelenerek envanter bilgileri, teknik çizimleri, kalıp çizimleri yapılmış ve irdelenmiştir.
ELAZIĞ YÖRESİ GELENEKSEL GİYİM KÜLTÜRÜNDE ERKEK YELEKLERİ